2022
DOI: 10.3390/ijerph19094937
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Social Media Use and Depressive Outcomes among College Students in China: Observational and Experimental Findings

Abstract: Aims: Problematic social media use is increasing in China and could be a risk factor for depression. We investigated cross-sectional associations between problematic social media use and depressive outcomes among Chinese college students with potential mediation by perceived social support, social media violence, and loneliness. Thereafter, we evaluated the effectiveness of a one-month group counseling intervention in reducing depressive symptoms related to social media addiction. Methods: Depressive symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The fear of COVID-19 and the lockdown’s impact were both associated with lower general wellbeing, anxiety and depression among Lebanese samples [ 58 , 59 ]. Results of our study showed that higher PSMU was significantly associated with depression and anxiety, in line with previous findings [ 60 62 ]. These authors speculated that the reason for this association may be due to the fact that individuals who engage in online-activities in an excessive way, may neglect healthy aspects of their lives, which could contribute to depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fear of COVID-19 and the lockdown’s impact were both associated with lower general wellbeing, anxiety and depression among Lebanese samples [ 58 , 59 ]. Results of our study showed that higher PSMU was significantly associated with depression and anxiety, in line with previous findings [ 60 62 ]. These authors speculated that the reason for this association may be due to the fact that individuals who engage in online-activities in an excessive way, may neglect healthy aspects of their lives, which could contribute to depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, excessive internet users may more be likely to replace their real-life interactions by online sites than the normal users. They were also found to have more depressive symptoms [ 61 , 62 ]. A study conducted on Lebanese university students had found a significant association between potential internet addiction and insomnia, depression, anxiety and stress [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that problematic social media use positively predicted loneliness 15 months later (Marttila et al, 2021). Chen et al (2022) study found that problematic social media use increased depressive symptoms and that loneliness mediates this relationship. Thus, state-FoMO may be associated with increased loneliness.…”
Section: Negative E Ects: the Mediating Role Of State-fomomentioning
confidence: 99%
“…The rst perspective posits that loneliness positively predicts problematic social media use [11,15,19,24]. The second perspective suggests that problematic social media use positively predicts loneliness [14,18]. The third perspective proposes a bidirectional relationship between loneliness and problematic social media use [16,17].…”
Section: The Causal Relations Between Loneliness and Problematic Soci...mentioning
confidence: 99%
“…First, there is a lack of longitudinal studies that explore the causal relationship between loneliness and problematic social media use. Existing research on the predictive direction of the relationship between loneliness and problematic social media use has yielded inconsistent ndings [11,[14][15][16][17][18][19]. It remains unclear whether loneliness precedes or follows problematic social media use.…”
Section: Introductionmentioning
confidence: 99%